2019
DOI: 10.3390/ijms20030778
|View full text |Cite
|
Sign up to set email alerts
|

The Metallome of Lung Cancer and its Potential Use as Biomarker

Abstract: Carcinogenesis is a very complex process in which metals have been found to be critically involved. In this sense, a disturbed redox status and metal dyshomeostasis take place during the onset and progression of cancer, and it is well-known that trace elements participate in the activation or inhibition of enzymatic reactions and metalloproteins, in which they usually participate as cofactors. Until now, the role of metals in cancer have been studied as an effect, establishing that cancer onset and progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 113 publications
(178 reference statements)
2
8
0
Order By: Relevance
“…Wach et al observed, among others, significantly increased levels of Ca, Cu, and Zn and decreased levels of Fe in serum of bladder cancer patients, and higher levels of serum P were found in lung cancer patients . Importantly, the serum Cu/Zn ratio has been shown to be a promising biomarker for lung cancer diagnosis, but other elemental ratios (e.g., V/Mn) might also be of diagnostic value for cancer . Overall, the existing literature is in line with our findings and points toward commonalities of specific elemental disturbances induced by the presence of a tumor.…”
Section: Resultssupporting
confidence: 91%
“…Wach et al observed, among others, significantly increased levels of Ca, Cu, and Zn and decreased levels of Fe in serum of bladder cancer patients, and higher levels of serum P were found in lung cancer patients . Importantly, the serum Cu/Zn ratio has been shown to be a promising biomarker for lung cancer diagnosis, but other elemental ratios (e.g., V/Mn) might also be of diagnostic value for cancer . Overall, the existing literature is in line with our findings and points toward commonalities of specific elemental disturbances induced by the presence of a tumor.…”
Section: Resultssupporting
confidence: 91%
“…Trace elements, especially metals, are regulators of cellular homeostasis and present key roles on pathological processes, such as cancer 19 . They function as cofactors, electron donors and are central for bioelectrogenesis and electrophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies that only examined the levels of specific elements in different body fluids and tumor tissues also reported statistically significant differences from the distribution of certain elements, such as decreased Zn and elevated Cu concentrations in serum, and decreased Fe and Mn levels in urine and tumor tissues of LC patients [ 145 , 146 , 147 ]. Based on previously published metallomic/ionomic results, a recent review discussed the critical role of metals in LC, especially the importance of high exposure of metals, metal homeostasis and interactions, and metal speciation in cancer onset and progression, which indicates the potential use of such information in early diagnosis, prognosis, or therapy for LC [ 148 ].…”
Section: Ionomics Of Complex Diseasementioning
confidence: 99%